2018
DOI: 10.1021/acs.iecr.8b00512
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Modificate Defects Engineering CdS Sphalerite-Wurtzite System for Efficient Photocatalytic H2 Evolution under Visible Light Irradiation

Abstract: According to quantum size effect and interface defects theory, the phase-modificate defects engineering photocatalyst MoS2/CdS-1/CdS-2 with smaller lattice mismatch degree was successfully designed through simple hydrothermal and solvothermal methods, in which sphalerite CdS-1 was nanoparticle (NP) while wurtzite CdS-2 was nanosheet (NS) shaped. The results showed H2 evolution activity was increased, which was about 20 times and 30 times those of MoS2/CdS-1 and MoS2/CdS-2, respectively. Also of note, it was 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…As shown in Figure e, the peaks at 162.6 and 161.5 eV are assigned to S 2– 2p 1/2 and S 2– 2p 3/2 in Bi 0 /BiOI­(001)/CdS, respectively, while they are located at 162.5 and 161.4 eV in Bi 0 /BiOI­(010)/CdS. In our previous study, the binding energies of Cd 2+ 3d 3/2 and Cd 2+ 3d 5/2 in pure CdS are located at 411.2 and 404.4 eV, while the binding energies of S 2– 2p 1/2 and S 2– 2p 3/2 are located at 161.7 and 160.6 eV, respectively . Therefore, the binding energies of Cd 3d and S 2p in Bi 0 /BiOI­(001)/CdS and Bi 0 /BiOI­(010)/CdS shifted positively, and the offsets of the latter is larger, which indicates that the interaction between components in Bi 0 /BiOI­(010)/CdS is stronger.…”
Section: Results and Analysismentioning
confidence: 71%
See 2 more Smart Citations
“…As shown in Figure e, the peaks at 162.6 and 161.5 eV are assigned to S 2– 2p 1/2 and S 2– 2p 3/2 in Bi 0 /BiOI­(001)/CdS, respectively, while they are located at 162.5 and 161.4 eV in Bi 0 /BiOI­(010)/CdS. In our previous study, the binding energies of Cd 2+ 3d 3/2 and Cd 2+ 3d 5/2 in pure CdS are located at 411.2 and 404.4 eV, while the binding energies of S 2– 2p 1/2 and S 2– 2p 3/2 are located at 161.7 and 160.6 eV, respectively . Therefore, the binding energies of Cd 3d and S 2p in Bi 0 /BiOI­(001)/CdS and Bi 0 /BiOI­(010)/CdS shifted positively, and the offsets of the latter is larger, which indicates that the interaction between components in Bi 0 /BiOI­(010)/CdS is stronger.…”
Section: Results and Analysismentioning
confidence: 71%
“…Qin et al fabricated BiOI/Bi 2 O 4 and found that BiOI is a perspective catalyst because of its appropriate optical properties and layered structure . BiOI is an anisotropic material, and the crystal structures observed from [001], [010], and [110] directions are shown in Scheme S2a–c. Some studies have found that the anisotropy of BiOI affects the degradation performance. , Tian et al studied the degradation performance of (001)-BiOI/(002)-g-C 3 N 4 and (110)-BiOI/(002)-g-C 3 N 4 + and found that BiOI(001) showed higher degradation activity . Pan et al found that BiOI(110) showed higher degradation activity as the (110) facet has a stronger adsorption capacity of oxygen molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable energy sources such as solar, wind, and nuclear energy sources are vital for anthropic life. Efficient use of solar energy is critical. Converting it into hydrogen would provide more fuel and reduce CO 2 emissions. It is well known that hydrogen energy exhibits a high calorific value, and it is widely applied in automobile industry. In recent years, many semiconductor materials, including two-dimensional (2D) materials, oxide semiconductors, transition-metal dichalcogenides, and transition-metal phosphates, were used for visible-light photocatalytic H 2 production. Especially, scientists found a lot of 2D materials such as Mo 2 S, g-C 3 N 4, layered double hydroxides (LDH), graphene, and graphdiyne (GDY) .…”
Section: Introductionmentioning
confidence: 99%
“…The most proficient ability of titanate-based nanotube materials is their efficient divalent cations’ ion-exchange capability. , The titanate nanotube that attains a high surface area has the ability to not only remove heavy metal ions and toxic metal compounds but also recover rare-earth metal ions, radioactive isotopes and adsorb dye molecules owing to their fascinating ion-exchange mechanism. , Most of the recent studies have shown the divalent metal-ion adsorption on titanate nanotubes. ,, To explore the advantages of titanate nanotubes, this study shows a synergistic approach of divalent metal-ion adsorption and nonmetal deposition at the inner pores of the nanotubes. Extending the traditional approach of monolayer deposition of CdS nanoparticles on metal oxides, we successfully demonstrate successive double-layered deposition of CdS nanoparticles within the inner pores of vertically aligned titanate nanotubes using the ion adsorption mechanism. ,, Several double-layered strategies have been reported so far; however, the dual CdS nanoparticles fashioned vertically aligned titanate nanotubes substrates for the conversion of incident solar visible light to energy has not been reported yet. …”
Section: Introductionmentioning
confidence: 99%